Physical Exercise in Patients with Severe Kidney Disease - Kosmadakis, G.C. (2010)
Patients with advanced chronic kidney disease (CKD), especially those on long-term dialysis, often suffer from muscle wasting and excessive fatigue. It is known that inactivity, muscle wasting and reduced physical functioning are associated with increased mortality in CKD. Known causes include uraemic myopathy and neuropathy, inactivity, and anaemia. Exercise in patients receiving regular dialysis treatment for end-stage renal disease was first introduced 3 decades ago, but is still only offered in a minority of renal units around the world, despite a significant body of evidence to support its use. Work is needed to increase awareness of the potential benefits of increased physical activity for patients with advanced CKD. This review summarizes the mechanisms of exercise intolerance and debility in advanced CKD patients, the methods used for the estimation of functional capacity, the options currently available for exercise training, and their influence on the well-being of this group of patients.